CYCLIC HYPERGROUPS WHICH ARE INDUCED BY THE CHARACTER OF SOME FINITE GROUPS - Sekhavatizadeh, Sara; Zahedi, Mohamad Mehdi; Iranmanesh, Ali (Italian Journal of Pure and Applied Mathematics, 2014)
Let G be a finite group and Ĝ be the set of all irreducible characters of G. In this paper, the hypergroups obtained from the character table Ĝ are considered. Moreover, we show that Ŝn for n ≥ 3 and Ân for n ≥ 4 are single-power cyclic hypergroups and D̂2n is cyclic with finite period.